Dual PI3K and Wnt pathway inhibition is a synergistic combination against triple negative breast cancer - Solzak, Jeffrey P.; Atale, Rutuja V.; Hancock, Bradley A.; Sinn, Anthony L.; Pollok, Karen E.; Jones, David R.; Radovich, Milan (NPJ breast cancer, 2017)
Triple negative breast cancer accounts for 15–20% of all breast cancer cases, but despite its lower incidence, contributes to a disproportionately higher rate of mortality. As there are currently no Food and Drug Administration-approved targeted agents for triple negative breast cancer, we embarked on a genomic-guided effort to identify novel targeted modalities. Analyses by our group and The Cancer Genome Atlas have identified activation of the PI3K-pathway in the majority of triple negative breast cancers. As single agent therapy is commonly subject to resistance, we investigated the use of combination therapy against compensatory pathways. Herein, we demonstrate that pan-PI3K inhibition in triple negative breast cancers results in marked activation of the Wnt-pathway. Using the combination of two inhibitors currently in clinical trial as single agents, buparlisib(pan-PI3K) and WNT974(WNT-pathway), we demonstrate significant in vitro and in vivo synergy against triple negative breast cancer cell lines and xenografts. Taken together, these observations provide a strong rationale for testing dual targeting of the PI3K and WNT-pathways in clinical trials. Therapeutics: Dual therapy shrinks triple negative breast tumors Two experimental drugs currently in clinical trials as single agents might work better together against triple negative breast cancer. Jeffrey Solzak and Milan Radovich, and colleagues from the Indiana University School of Medicine in Indianapolis, USA, analyzed gene expression data from cancerous and healthy breast tissues and from published genomic datasets. They found the PI3K pathway consistently activated in the majority of breast cancers that test negative for the three most common receptors known to fuel breast tumor growth. Inhibiting PI3K in these cells led to a marked increase in the activity of another critical pathway called Wnt, an observation that prompted the researchers to test a combination of a PI3K inhibitor, buparlisib, and a Wnt inhibitor, WNT974, in cell lines and xenograft models. Tumor cells shrunk more and mice lived longer than treatment with either agent alone.